2009
DOI: 10.4152/pea.200902143
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric and Spectroscopic Studies of Sulfonamide Azo-Dye Complexes with some Transition Metal Ions and Uranium

Abstract: Molecular structure of the azo-dye derived from sulfonamide was synthesized. The elucidation of ligand and complex structures were studied by electronic, infrared and 1H NMR spectroscopies. Proton-ligand constants of sulphonamid azo-derivatives and the stability constant of Mo (III), VO (II), UO 2 (II) and Co (II) metal ions with sulfonamide azodye derivatives have been determined potentiometrically in 0.1 M KCl and 30% (v/v) ethanol-water mixture. The data are discussed in terms of the electronic character of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Sulphonamides have long been used as drugs to treat leprosy, malaria, diabetes, cancer and tuberculosis, but more importantly in the context of this review, sulphonamide and azo‐sulphonamide derivatives have utility as ligands for a variety of metal cations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulphonamides have long been used as drugs to treat leprosy, malaria, diabetes, cancer and tuberculosis, but more importantly in the context of this review, sulphonamide and azo‐sulphonamide derivatives have utility as ligands for a variety of metal cations …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Sulphonamide derivatives inhibit CA through coordination of their SO 2 NH anion with the Zn 2+ cation of the enzyme, leading to a reduction in HCO − 3 synthesis in the transition state required for CA to function. 18,24 Sulphonamides have long been used as drugs to treat leprosy, malaria, diabetes, cancer and tuberculosis, 27 but more importantly in the context of this review, sulphonamide and azo-sulphonamide derivatives have utility as ligands for a variety of metal cations. [28][29][30][31][32] Among the drug families mentioned above, antibiotics are the most concerning because their high consumption and environmental release are the main causes of the spread of bacterial antibiotic resistance worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that sulfonamide derivatives are endowed with numerous therapeutic activities as anticonvulsants, HIV protease inhibitors, and antitumor agents [ 31 ]. Sulfonamide derivatives are also used for treating certain forms of malaria, urinary tract infections, erectile dysfunction [ 32 ] as well as use as herbicides and dyes [ 33 ]. Isoxazole derivatives also possess various interesting pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sulfonamides and azodye derivatives of sulfonamides were found to have a variety of biological properties such as anti‐tubercular, anticancer and antimalarial activities . Many sulfonamide azodye derivatives are usually applied as powerful ligands for a vast range of transition metal ions . The metal chelates find many applications in biological systems, dying processes and analytical detection of various metal ions .…”
Section: Introductionmentioning
confidence: 99%